Teachers’ Mindsets in Foreign Language Classrooms - Betül Oldaç; Selami Aydın (Literacy Trek, 2023)
This research aims to explore English teachers’ mindsets and further investigate whether teachers’ mindsets have anything to do with nine factors, namely, age, gender, the highest level of education completed, department graduated in, being abroad for education, receiving in-service training programs, teaching experience, level taught, and institution. In this descriptive study, data were collected from 162 English teachers working at geographically diverse institutions in Turkey through an online survey. The survey included a background questionnaire and a mindset instrument. Findings showed that more than half of the English teachers had a fixed mindset, and the remaining had either a mixed or a growth mindset, of which the latter constituted the smallest group in number. Results also revealed that teachers’ mindsets were irrespective of nine previously determined variables.